ANALISIS PEMASARAN TERNAK SAPI BALI SEMI INTENSIF DAN EKSTENSIF DI DESA LOPOK KECAMATAN LOPOK - Ardiansyah, Riyan; Hamdani, Asrul; Yani, Ahmad; Amrullah, Amrullah; Budiman, Cecep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the marketing system of Bali cattle under semi-intensive and extensive farming systems in Lopok Village, Lopok District, Sumbawa Regency. The analysis focuses on marketing channels, marketing margins, marketing efficiency, farmers’ share, and socio-economic factors affecting farmers’ income. Data were collected from Bali cattle farmers and marketing institutions involved in livestock distribution and were analyzed using descriptive quantitative and qualitative methods. The results of this study are expected to identify the most efficient marketing channels and provide a basis for developing strategies and policies to improve farmers’ welfare and support the sustainable development of Bali cattle agribusiness in Sumbawa Regency.